1997
DOI: 10.1359/jbmr.1997.12.7.1124
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of α5β1 Integrin in Matrix Interactions and Proliferation of Chondrocytes

Abstract: Integrins are cell surface receptors involved in cellular processes including adhesion, migration, and matrix assembly. In the present study, we analyzed the possible involvement of ␣5␤1 integrin in the regulation of chondrocyte adhesion, spreading, and proliferation. We found that rabbit growth plate chondrocytes were able to attach to substrates coated with type I collagen, type II collagen, or fibronectin within 24 h of culture. During this time period, attachment to fibronectin appeared to be dependent on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
86
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(91 citation statements)
references
References 33 publications
4
86
1
Order By: Relevance
“…Among the integrins expressed on chondrocytes, ␣5␤1 integrin is the one most studied to date. Previous studies have shown that this integrin regulates various aspects of chondrocyte biology (21)(22)(23)(24)(25). However, the involvement of this integrin in dedifferentiation was not supported by the results of the present study.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Among the integrins expressed on chondrocytes, ␣5␤1 integrin is the one most studied to date. Previous studies have shown that this integrin regulates various aspects of chondrocyte biology (21)(22)(23)(24)(25). However, the involvement of this integrin in dedifferentiation was not supported by the results of the present study.…”
Section: Discussioncontrasting
confidence: 99%
“…Chondrocytes express several types of integrins (17)(18)(19)(20), which are known to regulate various aspects of cell behavior. In addition to cell attachment, integrins on the chondrocytes are involved in proliferation, survival, differentiation, matrix remodeling, and response to mechanical stimuli (21)(22)(23)(24)(25). Integrins are also believed to play a role in the dedifferentiation of chondrocytes, but their involvement in the process has not yet been demonstrated.…”
mentioning
confidence: 99%
“…9A). Whether the cells attach to the polymer through binding to lysine groups, or through fibronectin synthesized by cells for attachment is as yet not clear [23]. Continuous culture of BMSC on polymers for 7 days showed that BMSC retained their morphology similar to the cells grown on tissue culture polystyrene (TCPS; data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Collagen type I is hydroxyproline-rich protein secreted in significant concentrations by BMSC cells [23,24]. Since collagen type I contains 10-15% hydroxyproline and it is the major protein synthesized by BMSC, we measured hydroxyproline contents in the culture supernatents to compare collagen synthesis in BMSC cultured on LDI-glycerol polymer or on the TCPS.…”
Section: Resultsmentioning
confidence: 99%
“…These ECM proteins may alter chondrocyte functions; FN and FN fragments have been reported to induce IL-1␤, IL-6, GM-CSF, matrix metalloproteinases (MMPs), and proteoglycan release in chondrocytes (5,6). Engagement of ␣ 5 ␤ 1 integrin by FN has also been implicated in chondrocyte adhesion, spreading, and proliferation in vitro (7,8).…”
mentioning
confidence: 99%